Safety assessment of equine allogeneic tenogenic primed mesenchymal stem cells in horses with naturally occurring tendon and ligament injuries - Carlier, Stephanie; Depuydt, Eva; Van Hecke, Lore; Martens, Ann; Saunders, Jimmy; Spaas, Jan H. (Frontiers in Veterinary Science, 2024)
• Objectives: The aim of this study was to evaluate the hematological, biochemical, immunological and immunomodulatory parameters following intralesional treatment with tenogenic primed equine allogeneic peripheral blood-derived mesenchymal stem cells (tpMSCs) in client-owned horses with naturally occurring superficial digital flexor tendon (SDFT) and suspensory ligament (SL) injuries. • Methods: The immunogenicity and immunomodulatory capacities of tpMSCs were assessed in a modified mixed lymphocyte reaction, including peripheral blood mononuclear cells (PBMCs) of 14 horses with SDFT and SL injuries after treatment with tpMSCs. In a second study, 18 horses with SDFT and SL injuries received either an intralesional injection with tpMSCs (9) or no treatment (9). Clinical pathology was evaluated before treatment, on day 7 and 21 after treatment. • Results: The tpMSCs did not provoke a cellular immune response (P<0.001) and were able to immunomodulate stimulated T lymphocytes (P<0.001) in vitro. Therapeutic use of tpMSCs did not result in relevant hematologic or biochemical abnormalities. • Main limitations: Both studies had a small sample size. No statistical analyses were performed in the second study. Fibrinogen was only analyzed in a single horse prior to treatment. • Conclusions: Co-incubation of tpMSCs and PBMCs of horses that have been previously exposed to tpMSCs did not elicit a cellular immune response and tpMSCs were able to immunomodulate stimulated T lymphocytes. Intralesional treatment with tpMSCs did not provoke abnormal changes in hematological and biochemical parameters.